Artificial Intelligence and learning, epistemological perspectives - C. T. A. Schmidt (AI & Soc (2007) 21:537-54, 2007)
In this article, I establish a theory of knowledge approach for evaluating the use of computers for educational purposes at the university. In so doing, I trace part of the history of the ``enabling factor'' of Artificial Intelligence in this sector, an important element that has been integrated into everyday learning environments. The result of my reflection is a dialogical structure, directly inspired by past technology assessment research, which illustrates the conceptual advancement of researchers in the field of learning technologies. The notions covered have implications in future policy-related discourse with regards to education.